Competency-Based Education at a Madrasah Aliyah in Sumedang: Eliciting the Organized Programs - Rifqi Syauqi Hubby; Diding Nurdin; Asep Suryana (STAI Hubbulwathan Duri, 2022)
The competency-based education program is a flagship program launched by a Madrasah Aliyah (or, MA; Islamic based senior high school) in Sumedang to produce graduates who are competent and skillful, especially in the automotive, culinary, fashion, and technology. Students are expected to be able to compete in the professional fields. In this article, the implementation of the program is discussed, which is seriously trying to increase the competence of graduates. The method used in this present study is a mixed method with the techniques of documentation, observation studies and questionnaires to determine the students' number of inputs, their interest in the competency program in that school, and the existing programs. The results show that 100% of the students chose and followed the competency program according to their desires and talents, and because of willingness to get better opportunities after graduating. Moreover, it was found that the four competences offered have increased students’ participation in learning. Future recommendations are provided in this article.